Japan : Financial Sector Assessment Program-Technical Note-Systemic Risk Analysis and Stress Testing the Financial Sector. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the results of stress testing of the financial sector in Japan. The Japanese financial system appears generally resilient to short-term risks, but pockets of vulnerability exist. Overall, banks appear to have sufficient capital and liquidity buffers to cope with a scenario of severe recession owing to disruptions in global trade, and accompanied by a sharp increase in interest rates and risk premiums, and a decline in equity prices. Spillovers within the system also appear to be limited. At the same time, resilience is not equal among all institutions included in the analysis. Some life insurance companies and regional banks may need to strengthen their capital buffers.